In Vitro Metabolizable Protein and Utilizable Amino Acid Estimation of Ruminant Feed Ingredients - Prusty, Sonali; Sharma, Vijay Kumar; Sontakke, U. B.; Kundu, S. S. (Indian Journal of Animal Nutrition, 2019)
Present study was conducted to estimate in vitro metabolizable protein (IVMP) and utilizable amino acid (uAA) content of ruminant feed ingredients like grains viz. maize, red sorghum, pearl millet and barley; agro-industrial byproducts viz. wheat bran, rice bran, gram churi and maize gluten meal (MGM); oilseed cakes viz. groundnut cake-deoiled (DGNC), mustard cake-deoiled (DOMC) and cotton seed cake (CSC) and fodders viz. maize green, sorghum green, pearl millet green, berseem fodder and wheat straw. The samples were incubated in nine replicates. Three replicates followed filtration of incubation mixture and N estimation in the filtrate and residue and Ammonia N estimation in the filtrate. Ammonia N was subtracted from total N in filtrate and residue to obtain utilizable crude protein (uCP). Rest of the incubated replicates were freeze dried to obtain residue with CP concentration equivalent to that of uCP, of which half number of samples were subjected to amino acid analysis. From uCP, methionine and lysine availability among grains ranged from 1.21 to 2.01% and 2.28 to 4.52%, respectively. The utilizable methionine (% CP) and lysine (% CP) from agro-industrial byproducts was highest from maize gluten meal (MGM; 1.82) and rice bran (5.27), respectively. Methionine (% CP) availability from groundnut cake-deoiled (DGNC; 0.74) and mustard cake-deoiled (DOMC; 0.89) were lower than that of cottonseed cake (CSC; 2.40) and soybean meal (SBM; 2.85). Rest of the sample residues were subjected to hydrolysis with pepsin and pancreatin for estimation of intestinal digestibility of uCP. Intestinal digestibility was multiplied with uCP to obtain in vitro metabolizable protein (IVMP). The regression equation developed upon regressing estimated MP (IVMP) from calculated MP derived from protein fractions as per CNCP system was IVMP = 0.915Ã— calculated MP + 1.489 (R2 = 0.934 at P